(3cJGH GdJHjGfs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI(B: (3heeG hLO ai HYV eUGMa GdTGejjf(B: (3HSe Gddg GdBMO GdUeO GdNGdb GdPi de jdO hde jhdO s
(3BNQgG (B:s
(3Mi jJVM dg cPdc eHjf LejY eGajg aGYQa Pdc Ef TGA Gddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B52 - (3U(B56s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B103 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B105s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B104 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs